2001
DOI: 10.1144/jgs.158.5.801
|View full text |Cite
|
Sign up to set email alerts
|

Direct dating of authigenic K-feldspar overgrowths from the Kilombero Rift of Tanzania

Abstract: K-feldspars form important detrital and authigenic components in sediments but may be difficult to separate by conventional means for isotope analysis, particularly geochronology. UV lasers are being increasing applied to in situ analysis since they are strongly absorbed by clear minerals such as K-feldspar, and can achieve a spatial resolution of better than 20 m for individual Ar/Ar analyses. Here we demonstrate separation of detrital K-feldspar with a mean age of 423 14 Ma and authigenic overgrowths with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 19 publications
0
17
0
4
Order By: Relevance
“…Despite the fact that previous investigations (Hagen et al, 2001) have yielded meaningful Ar-Ar ages for authigenic K-feldspar, it has been suggested that authigenic K-feldspar does not quantitatively retain Ar at low temperatures (Lee and Parsons, 2003). Therefore, the retentiveness of authigenic K-feldspar with respect to Ar had to be quantified in detail in order to support the Ar-Ar data.…”
Section: Ar-ar Geochronologymentioning
confidence: 94%
“…Despite the fact that previous investigations (Hagen et al, 2001) have yielded meaningful Ar-Ar ages for authigenic K-feldspar, it has been suggested that authigenic K-feldspar does not quantitatively retain Ar at low temperatures (Lee and Parsons, 2003). Therefore, the retentiveness of authigenic K-feldspar with respect to Ar had to be quantified in detail in order to support the Ar-Ar data.…”
Section: Ar-ar Geochronologymentioning
confidence: 94%
“…The main reason is that the sediments are infiH deposits in Pleistocene caverns within a karstic terrain of the Sierra de Atapuerca, and thus contain no heated minerals amenable to Ar-Ar and fission-track dating. However, aU[nIgelnIC minerals Ar-Ar methods Dickin, 1997;McDougaH and Harrison, 1999;Hagen et al, 2001) may be po��slt)(e, and unheated quartz methods Dickin, 1997;Gosse and 2001;Anthony and Granger, 2007) is possible (CarboneH et al, 2008). Several of the deposits are within the 50-400-kyr age range of conventional U-Th-series dat (e.g., Dickin, 1997;Ku, 2000), and within the somewhat age range of of tooth enamel Rink, 1997).…”
mentioning
confidence: 99%
“…More recently, Kelley et al (1994) developed an ultraviolet (UV) laser ablation system which has high spatial resolution (b 20 μm) and the UV light is strongly absorbed by K-feldspar. Hagen et al (2001) demonstrated the potential of this method by successfully dating K-feldspar authigenesis. With its high spatial resolution, UV laserprobe can target and ablate specific areas of the K-feldspar cements.…”
Section: Ar-ar Datingmentioning
confidence: 97%
“…Lee and Parsons (2003) suggested that authigenic K-feldspar will leak radiogenic Ar at the temperatures experienced during burial in sedimentary basins. Although Ar loss is evident within sub-grained high temperature feldspar (Parsons and Brown, 1988), UV laserprobe dating of authigenic K-feldspar has yielded meaningful ages (Hagen et al, 2001) indicating that they may, in some cases, retain argon quantitatively. Sherlock et al (2005) concluded that because authigenic microtextures are produced by subgrain nucleation and growth (Worden and Rushton, 1992), rather than by transformation, cooling or deformation mechanisms, subgrains formed at, or below, their closure temperature (T c , temperature of a system at the time given by its age) will retain argon in many natural low temperature systems.…”
Section: Ar Diffusionmentioning
confidence: 99%